Dynamic informative advertising of new experience goods - Saak, Alexander E. (Wiley, 2012)
This paper analyzes the optimal advertising and price policies of a monopolist who sells a new experience good over time to a population of heterogeneous forward‐looking buyers. We consider advertising that can complement or substitute for learning‐by‐purchasing, and we show that the advertising intensity always peaks during the early stages when the price extracts surplus from the buyers who are yet to learn their valuation for the good. We also show that even though informative advertising may temporarily raise prices and slow down the learning process, an advertising ban can reduce welfare.